2018
DOI: 10.1093/mnras/sty3357
|View full text |Cite
|
Sign up to set email alerts
|

The suppression of star formation on the smallest scales: what role does environment play?

Abstract: The predominantly ancient stellar populations observed in the lowest mass galaxies (i.e. ultrafaint dwarfs) suggest that their star formation was suppressed by reionization. Most of the well-studied ultra-faint dwarfs, however, are within the central half of the Milky Way dark matter halo, such that they are consistent with a population that was accreted at early times and thus potentially quenched via environmental processes. To study the potential role of environment in suppressing star formation on the smal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 118 publications
3
29
1
Order By: Relevance
“…Our results agree with studies that have found that satellite survival depends on host-satellite distance at pericentric passage (e.g. D' Onghia et al 2010;Zhu et al 2016;Sawala et al 2017;Garrison-Kimmel et al 2018b;Nadler et al 2018;Rodriguez Wimberly et al 2019). We note that the destruction that we see is somewhat less extreme than in Garrison-Kimmel et al (2017b), who used two of our baryonic simulations (m12i and m12f) and found no surviving subhalos at z = 0 within ∼20 kpc of the host.…”
Section: Comparison With Dark Matter-only Simulationssupporting
confidence: 92%
“…Our results agree with studies that have found that satellite survival depends on host-satellite distance at pericentric passage (e.g. D' Onghia et al 2010;Zhu et al 2016;Sawala et al 2017;Garrison-Kimmel et al 2018b;Nadler et al 2018;Rodriguez Wimberly et al 2019). We note that the destruction that we see is somewhat less extreme than in Garrison-Kimmel et al (2017b), who used two of our baryonic simulations (m12i and m12f) and found no surviving subhalos at z = 0 within ∼20 kpc of the host.…”
Section: Comparison With Dark Matter-only Simulationssupporting
confidence: 92%
“…If baryonic effects act to create or destroy planes of satellites, then dark matter-only simulations may not be able to wholly capture the theoretical picture of satellite plane formation. The central disk in baryonic simulations tidally destroys satellites, altering their radial profile at small distances from the host (e.g., D'Onghia et al 2010;Sawala et al 2017;Garrison-Kimmel et al 2017;Nadler et al 2018; Kelley et al 2018;Rodriguez Wimberly et al 2019;Samuel et al 2020). This leads the surviving satellites to have more tangentially biased orbits (Garrison-Kimmel et al 2017, 2019a, but these effects do not necessarily imply an effect on planarity.…”
Section: Introductionmentioning
confidence: 99%
“…The radial velocity of TucanaII has been measured (Walker et al 2016), but no spectroscopy is available for the other three systems, so the viability of their association with each other or with the Magellanic Clouds has not been tested. Finding dwarf galaxies that formed with only other dwarfs as their neighbors will enable novel tests of the effects of environment on early galaxy formation and evolution (e.g., D'Onghia & Lake 2008; Wetzel et al 2015;Fillingham et al 2019;Rodriguez Wimberly et al 2019).…”
Section: Introductionmentioning
confidence: 99%